Knowledge Regarding Childhood Injury Among Mothers of Under 5 Children - Kandel, Bhawana (Ganeshman Darpan, 2026)
An injury refers to physical harm to the human body that occurs when it is exposed to a level of force exceeding its normal physiological capacity to withstand it. Injuries in childhood represent a significant public health concern, as they contribute greatly to illness, disability, and death among children. The present study aimed to assess the knowledge regarding childhood injury among mothers of under 5 children in Tulsipur municipality ward number 1 of Dang. A descriptive cross sectional study was conducted among 88 mothers by adopting purposive sampling technique. Semi structured interview schedule was developed which consisted of two parts. Face to face Interview was taken in their feasible time, approximately 25-30 minutes’ time was given. The data were analyzed through descriptive statistics (frequency, percentage) and inferential statistics (Chi-square). The result of the study showed that only 13(14.8%) of the respondents have low level of knowledge, 50 (56.8%) have moderate knowledge and 25 (28.4%) have high level of knowledge about childhood injury There was no statistically significant association between level of knowledge and selected socio demographic variable which are age, occupation and education. Thus, the study concluded that more than half of respondents had moderate level of knowledge Therefore, the study recommends providing mass education program in the community regarding injury prevention.